2014
DOI: 10.1007/s00248-014-0538-7
|View full text |Cite
|
Sign up to set email alerts
|

Successional Change in Microbial Communities of Benthic Phormidium-Dominated Biofilms

Abstract: Benthic cyanobacterial blooms are increasing worldwide and can be harmful to human and animal health if they contain toxin-producing species. Microbial interactions are important in the formation of benthic biofilms and can lead to increased dominance and/or toxin production of one or few taxa. This study investigated how microbial interactions contribute to proliferation of benthic blooms dominated by the neurotoxin-producing Phormidium autumnale. Following a rainfall event that cleared the substrate, biofilm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 58 publications
6
43
2
Order By: Relevance
“…A. minutissimum is reported as a pioneering species during the initial processes of biofilm formation (Sekar et al, 2004;Leinweber and Kroth, 2015). It is often the most numerous diatom occuring in P. autumnale and P. favosum-dominated microbial mats (Kelly, 2012;Brasell et al, 2015), as was the case in Krčić Spring, where it could efficiently utilise potency by forming pads and stalks, thus additionally anchoring the biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…A. minutissimum is reported as a pioneering species during the initial processes of biofilm formation (Sekar et al, 2004;Leinweber and Kroth, 2015). It is often the most numerous diatom occuring in P. autumnale and P. favosum-dominated microbial mats (Kelly, 2012;Brasell et al, 2015), as was the case in Krčić Spring, where it could efficiently utilise potency by forming pads and stalks, thus additionally anchoring the biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Both P. crispa and P. autumnale increased their proportion in the habitat in the direction of places more distant to Uria lomvia and Rissa tridactyla colonies. Phormidium autumnale is a species with a wide spectrum of occurrence in polar regions Strunecký et al 2010) and prefers sites with higher nitrogen concentrations but does not occur in sites with high phosphorus concentrations (Heath et al 2014;Brasell et al 2015). Similarly, Prasiola crispa is a typical species in cold-temperate regions, where it is usually associated with habitats rich in organic nitrogen (Graeve et al 2002;Holzinger et al 2006;Matuła et al 2007;Richter et al 2009;Broady et al 2012;Richter et al 2014Richter et al , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…That's to say, the metabolic activity of the same algal species changes with the environmental conditions. Microbial succession in biofilms was found to be driven by bacteria in the early stages, and the initial attachment of bacteria to substrate surface was random (Brasell et al, 2015). Previous studies reported that the succession of bacterial assemblages in biofilms was mostly determined by the age of biofilms (Artigas et al, 2012).…”
Section: Discussionmentioning
confidence: 99%